The significance of technology-driven entrepreneurship activities: Lessons from SMEs operating in the manufacturing industry - Anil Yigit; Dominik K. Kanbach (Cogent Business & Management, 2023)
Innovation in small and medium enterprises (SMEs) is often the result of technology-driven or market-pull entrepreneurship activities. So far, although its importance in practice, as well as in academia continues to grow, extant research exhibits little theory about the process of technology-driven entrepreneurship in SMEs. The study aims to better understand how technology-driven entrepreneurship processes transform business in SMEs in the manufacturing industry. Therefore, we developed a technological entrepreneurship (TE) process framework by utilizing the flexible pattern matching approach (FPMA). We iteratively compared a priori patterns from existing theoretical knowledge to empirical findings that emerged from in-depth interviews with corporate executives in the manufacturing industry. The framework highlights the TE process in SMEs leading to four output components: (1) corporate-function-related, (2) business-model-related, (3) competitiveness-related, and (4) customer-related. This study makes a unique contribution to academia by being the first that develops a TE process framework tailored to SMEs from the manufacturing industry. We point out that sustainable growth and competitiveness of SMEs depends on appropriate TE process management, and we underline the strategic importance of TE-driven transformation for SME managers. Our study expands the scope of TE and SME research and provides empirically grounded insights into technology-driven innovation.
Keywords: 650; small and medium enterprises; innovation; flexible pattern matching approach; technological entrepreneurship; Technology-driven entrepreneurship